Urban citizenship in Africa South of the Sahara: Comments on Maarten Prak’s Citizens without Nations - Coquery-Vidrovitch, Cathérine (TSEG - The Low Countries Journal of Social and Economic History, 2020)
This article argues that the defining features of urban citizenship as described by Maarten Prak for Europe, Asia and the Americas, were also present in the cities that emerged in Africa south of the Sahara well before the colonial era. It discusses the forms that citizenship in Africa took, paying special attention to the question whom were qualified as citizens.